Decision Support System By Applying Exponential Comparison Method (ECM) In Selecting The Best Village Secretary In Pondok Kelapa Sub-District - Silvia Wahyu Hastuti; Liza Yulianti; Lena Elfianty (Penerbit Jurnal Indonesia, 2024)
The selection of the best village secretary in Pondok Kelapa Sub-District is carried out directly by the sub-district. In determining the best village secretary, Pondok Kelapa Sub-District is considered ineffective, as it is challenging to decide who is suitable to become the best village secretary. The decision support system application determines the best village secretary candidate in Pondok Kelapa Sub-District using the Exponential Comparison Method (ECM). The first step is to assign weights to each criterion, followed by ranking to determine the highest alternative from all available alternatives. This highest alternative is the result worthy of being accepted as a tested village secretary based on the predetermined criteria. This study concludes that the system built can assist the sub-district in selecting a village secretary who meets the standards, thus enabling them to carry out the tasks and responsibilities assigned to the village secretary.